2021
DOI: 10.1111/1365-2435.13977
|View full text |Cite
|
Sign up to set email alerts
|

Topography in tropical forests enhances growth and survival differences within and among species via water availability and biotic interactions

Abstract: 1. Topography is associated with variation in soil water, biogeochemical properties and climate, which drive diversity by filtering species and promoting niche differences. However, the potential for topography to promote fitness differences and diversity among tree species and populations remains poorly tested in tropical rainforests, especially at small spatial scales in everwet climates.2. We reciprocally transplanted tree seedlings between ridge and riparian sites and manipulated neighbour abundance and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 95 publications
3
15
0
Order By: Relevance
“…Despite research suggesting that negative plant–soil feedbacks are more limiting for rare species in some neotropical trees [39], the stronger negative effects of CDD on P. malaanonan indicates that negative CDD is probably limiting population growth of the most abundant species at our study sites. The cause of the sustained negative conspecific neighbour effects on D. lanceolata are unclear, but compared with other dipterocarps, seedling and sapling growth of D. lanceolata was the most sensitive to neighbour abundance in a parallel study at our study sites [15]. Our results, therefore, align with an emerging perspective that this species is disproportionately sensitive to conspecific neighbour density.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Despite research suggesting that negative plant–soil feedbacks are more limiting for rare species in some neotropical trees [39], the stronger negative effects of CDD on P. malaanonan indicates that negative CDD is probably limiting population growth of the most abundant species at our study sites. The cause of the sustained negative conspecific neighbour effects on D. lanceolata are unclear, but compared with other dipterocarps, seedling and sapling growth of D. lanceolata was the most sensitive to neighbour abundance in a parallel study at our study sites [15]. Our results, therefore, align with an emerging perspective that this species is disproportionately sensitive to conspecific neighbour density.…”
Section: Discussionsupporting
confidence: 84%
“…The stronger effect of negative density dependence on growth than survival in these two species may be the result of their high survival rates in general relative to other dipterocarps [24]. The rank order of the survival response of species to density dependence found in our study is consistent with previous research on these species [15]: survival of P. malaanonan was most sensitive to…”
Section: (B) Consistent Positive Conspecific Density-dependent Recrui...supporting
confidence: 90%
“…Nonetheless, it is remarkable that mature bigcone trees, particularly at low elevations, are frequently distributed in canyon, riparian settings as reported by the united states forest service (USFS) (Howard, 1992). Other studies have also found strong effects of hillslope position on seedling survivorship and forest composition, leading us to expect that our manipulation simply may not have captured the full strength of these differences between ridges and canyon bottoms (Frey et al, 2007;O'Brien and Escudero, 2022). Our downslope plots were lower but by no means equivalent to a riparian planting.…”
Section: Elevationmentioning
confidence: 74%
“…Unfortunately, most current studies focus on large-scale topography with elevation differences of hundreds or even thousands of meters, such as the Changbai Mountains ( Wang et al., 2013 ; Yu et al., 2013 ; Yu and Liu, 2020 ) and the Alps ( Pappas et al., 2020 ), and there is a lack of research on small-scale topography. However, it has been demonstrated that these effects remain even on microtopography with elevation differences of less than 100 m ( Galicia et al., 1999 ; Ma et al., 2020 ; O’Brien and Escudero, 2022 ). Furthermore, plantations spread widely in hilly areas with a small elevation difference.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of microtopography on the distribution of climatic factors is also extant ( Mei et al., 2018 ; Esteban et al., 2021 ), or even greater ( Wang et al., 2020 ; O’Brien and Escudero, 2022 ), when precipitation decreases or even drought. The resilience index and its components, resistance and recovery indices, are commonly used to evaluate the effect of drought on plant growth.…”
Section: Introductionmentioning
confidence: 99%